Addressing Childhood Obesity in Brunei Darussalam: Proposing Rights-Based Legal and Policy Reforms - Ahmad, Nehaluddin; Haji Ahmad, Siti Sara; Shamsu, Lilly Suzana; Ali, Aqilah Walin; Lilienthal, Gary L (Fakultas Hukum, Universitas Muhammadiyah Yogyakarta, 2026)
Childhood obesity is a growing public health concern in Brunei Darussalam, highlighting the urgent need for effective intervention. While public health initiatives have traditionally addressed these challenges, there is increasing recognition of the role of legal and policy measures in promoting healthier environments for children. This study advances existing scholarship by examining Brunei’s legal and policy frameworks through a child rights and right-to-health perspective, evaluating whether they effectively safeguard children’s right to health. Using a qualitative, doctrinal legal methodology, the research analyses relevant domestic legislation and key policy instruments, supported by comparative insights from international best practices and guided by the right to health, the precautionary principle, and the best interests of the child. The study finds that although Brunei has introduced voluntary marketing codes, healthy school canteen guidelines, and sugar-sweetened beverage taxes, the framework remains fragmented and largely non-binding. To effectively prevent childhood obesity, Brunei should adopt binding regulations on food marketing to children, enforce statutory nutrition standards in schools, introduce front-of-pack labellinglabeling, and expand sugar-related fiscal measures within a clear legal framework. This study therefore, therefore, offers a novel, rights-based perspective to inform more coherent and effective public health reform.